2015
DOI: 10.4028/www.scientific.net/amm.806.302
|View full text |Cite
|
Sign up to set email alerts
|

Importance and Role of Internal Communication in Organizations

Abstract: Market liberalization has accelerated and strengthened the pressure of competitors in an open struggle for the retention of existing and favor of new clients. It is necessary to understand the importance and necessity of good business communication, because if business communication in the organization is at a higher level, then the relationship between the organization and its clients is at a higher level as well. Employees in the organization are the ones who represent it, so if the internal communication in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
(12 reference statements)
1
9
0
1
Order By: Relevance
“…The model facilitated in understanding the concept of employee engagement. The finding of the study were congruent with existing literature (Ababneh et al, 2019;Bekirogullari, 2019;Bharadwaj, 2014;Chmielecki, 2015;Croonen, 2010;Eskelinen et al, 2017;Gagnon et al, 2009;Gupta and Sharma, 2016;Mansoor and Hassan, 2016;Martinez and Hurtado, 2018;Mazzei and Ravazzani, 2014;McBain, 2007;Men, 2014;Mishra et al, 2014;Neill, 2015;Saunders and Thornhill, 2004;Stevanovic and Gmitrovic, 2015;Vercic and Vokic, 2017). The findings of the study facilitated in proving that the formulated hypothesis should be accepted.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The model facilitated in understanding the concept of employee engagement. The finding of the study were congruent with existing literature (Ababneh et al, 2019;Bekirogullari, 2019;Bharadwaj, 2014;Chmielecki, 2015;Croonen, 2010;Eskelinen et al, 2017;Gagnon et al, 2009;Gupta and Sharma, 2016;Mansoor and Hassan, 2016;Martinez and Hurtado, 2018;Mazzei and Ravazzani, 2014;McBain, 2007;Men, 2014;Mishra et al, 2014;Neill, 2015;Saunders and Thornhill, 2004;Stevanovic and Gmitrovic, 2015;Vercic and Vokic, 2017). The findings of the study facilitated in proving that the formulated hypothesis should be accepted.…”
Section: Resultssupporting
confidence: 88%
“…Study results revealed that strategic change failure occurs when the employees fail to promote effective internal communication that is associated with increased employee engagement. Similar to existing research conducted in large organisations, internal communication is essential in organisations and motivates the employees' to support the decision the proposed strategic change (Bharadwaj, 2014;Eskelinen et al, 2017;Martinez and Hurtado, 2018;Neill, 2015;Stevanovic and Gmitrovic, 2015). It is essential to involve employees at every level of strategic communication to avoid uncertainty, fear, and lack of trust.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…To define internal organizational communication, it can be stated that internal business communication refers to the communication between people who are employed in an organization or between components of an organization or between management and employees. Internal organization communication contains all communicative and information activities among the members of an organization (Stevanovic & Gmitrović, 2015). The author of the present essay suggests that internal communication in a company detects an essential communication network of a company.…”
Section: Organizational Communicationmentioning
confidence: 85%